Attenuation of neutrophil adhesion and formation of neutrophil extracellular traps by pooled human immune globulins - Vidhya R. Rao; Vidhya R. Rao; Sana Iqbal; Bradford A. Young; Christine Mun; Christine Mun; Sandeep Jain; Sandeep Jain; Simon Kaja; Simon Kaja; Simon Kaja (Frontiers in Pharmacology)
IntroductionThis study investigated the efficacy of pooled human immune globulins (Flebogamma® DIF) to combat the formation of neutrophil extracellular traps (NETs) and NETosis, along with neutrophil adhesion to corneal epithelial cells in response to dry eye disease relevant stimuli.MethodsHuman neutrophils were isolated by bead-based immunomagnetic depletion of non-target cells from human whole blood. NETosis was induced using phorbol 12-myristate 13-acetate (PMA) or anti-citrullinated histone 4 R3 antibody (H4R3 ACPA). Extracellular DNA was used as a surrogate biomarker of NETosis, and it was quantified using a 96-well, plate reader-based fluorescent assay and by confocal microscopy in 8-well chambers using the DNA dye, SYTOXTM Green. Neutrophils were labeled with calcein-AM and adhesion to human corneal epithelial cells was measured. The efficacy of a dose-range of pooled human immune globulin (Flebogamma® DIF, 0.01%–5%) was tested in all assays.ResultsPooled human immune globulins (Flebogamma® DIF) dose-dependently inhibited both PMA and H4R3 ACPA induced NETosis, with concentrations ≥2.5% fully preventing release of extracellular DNA over a 2–16 h time period. Similarly, Flebogamma® 5% DIF prevented NETosis against PMA (20 nM) and a dose range (0.1–10 μg/mL) of H4R3 ACPA. Both PMA and H4R3 ACPA increased adhesion of neutrophils to corneal epithelial cells by 20% and 5%, respectively. Flebogamma® DIF treatment resulted in a dose-dependent reduction of neutrophil adhesion, with Flebogamma® 5% DIF reducing adhesion to baseline levels.DiscussionThese findings show the dose-dependent efficacy of pooled human immune globulins, specifically Flebogamma® DIF against experimentally and pathologically induced NETosis and neutrophil adhesion to corneal epithelial cells, in vitro. The results from this study support the continued clinical development of Flebogamma® 5% DIF as a novel and efficacious treatment for the signs and symptoms of dry eye disease.